Encyclopedic dictionary of environment - Bharal, Chavvi (AITBS, 2006)
Instead of merely being concerned about the environment, be knowledgeable. Until now, anyone who wanted information about the environmental crisis was forced to turn to sources in dozens of different fields (chemistry, biology, demography, physics, geology, oceanography, industrial technology, and many more). Encyclopedic Dictionary of the Environment provides information from all these scientific fields in jargon-free language that the layperson can easily understand. Over 2000 entries explain the causes and effects of polution in every form, scientific concepts behind environmental theory, the technological problems involved, and the solutions that are being developed, tested, accepted,or sometimes rejected